The prevalence between stress and acne vulgaris among medical students at Universitas Udayana in the 2019 period - Somia Sri Subramaniam; Anak Agung Gde Putra Wiraguna; Ni Luh Putu Ratih Vibriyanti Karna (Intisari Sains Medis, 2021)
Background: Acne vulgaris is a common disease in medical students. One of the causes of acne vulgaris is stress. Acne vulgaris can affect the quality of life associated with one's self-confidence. But often, this disease is ignored and not treated properly. This study aims to know if acne vulgaris occurs in students at the Faculty of Medicine, Universitas Udayana, Bali, Indonesia, related to the stress that affects acne vulgaris.Methods: This research is a descriptive cross-sectional study. Data is collected using a data retrieval form. The inclusion criteria in this study were: 1) Participants selected must be from English class from semester 7 and aged 20 or above; 2) Participants can be from both genders; and 3) Participants that join the study willingly. Besides, the exclusion criteria were respondents who did not approve as a research sample and did not fill out informed consent. Data were analyzed using SPSS version 17 for Windows.Results: About 62 of 93 study participants were diagnosed with acne vulgaris in students at the Faculty of Medicine, Universitas Udayana. There were 31 of 62 study participants who were diagnosed with acne vulgaris due to stress. Women had more acne vulgaris than men and the number of students that had acne vulgaris the most are at the age of 21. The most common type of lesion is comedonal with a mild classification level. Most of the subject's cause of acne due to stress is before block exam. Most of the participants feel embarrassed due to acne. About 24.2% of the subjects had a habit of scratching/squeezing acne vulgaris.Conclusion: Most of the subjects diagnosed with acne were female and age 21 years old. Besides, comedones were the predominant type of lesion, followed by a mild degree of acne severity.